1989
DOI: 10.1108/eum0000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Education Management: Part One

Abstract: Learning styles, categorised after Kolb, are analysed in a group of schoolteachers who occupied managerial roles by means of a Learning Style Questionnaire. The results are compared to those in the literature for managers in general. Amongst teachers, women and primary school managers were found to be stronger in their tendency to be Activists and Pragmatists, senior managers to be Pragmatists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
3
4
2
Order By: Relevance
“…The learning styles of individuals usually change over time; therefore, such differences between different age groups are expected. The results of the present study corroborate the findings of Fleming et al (2011) who found significant relationships between some learning styles and students’ age, the findings of Seymour and West-Burnham (2007) who asserted that there is a relationship between learning styles and age, as well as those of Kayes (2005) who suggested that age influences learning style preferences. However, the results of this study are in contrast to those of a number of previous studies which found no link between age and student’s learning style preferences (Pallapu, 2008; Gappi, 2013; Yousef, 2014).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The learning styles of individuals usually change over time; therefore, such differences between different age groups are expected. The results of the present study corroborate the findings of Fleming et al (2011) who found significant relationships between some learning styles and students’ age, the findings of Seymour and West-Burnham (2007) who asserted that there is a relationship between learning styles and age, as well as those of Kayes (2005) who suggested that age influences learning style preferences. However, the results of this study are in contrast to those of a number of previous studies which found no link between age and student’s learning style preferences (Pallapu, 2008; Gappi, 2013; Yousef, 2014).…”
Section: Resultssupporting
confidence: 90%
“…In their study, Seymour and West-Burnham (2007) analyzed the learning styles of teachers who hold managerial posts in schools. Results indicated that managers in schools and colleges displayed a similar spread of learning styles to those of their counterparts in industry and commerce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, our results in Table 3 also showed that there are statistically significant differences between the three age groups and theorist learning style. The results corroborate the conclusions of [39] who suggested that age influences preferences in terms of learning style, as well as those of [40] who stated that there is a relationship between learning styles and age and also the conclusions of [41] who found significant relationships between certain learning styles and students age. Nonetheless, these findings contrast with a number of previous studies that have found no relation between age and student learning style preferences [42-37-43].…”
Section: Age Effectsupporting
confidence: 89%
“…The Theorist preferred learning style focuses on analysing and synthesising information, while people with a Pragmatist learning style preference need to see the direct application of their learning in helping plan practical solutions to their problems. The Honey and Mumford model has been applied to the educational sector with school managers in eliciting their learning style preference, with a follow-up study using a diagnostic questionnaire to clarify subjects' learning orientation (Seymour & West-Burnham, 1989Kelly, 1995).…”
Section: Honey and Mumford Learning Style Modelmentioning
confidence: 99%